2021
DOI: 10.1111/ffe.13454
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residual stress distribution and microstructural characteristics on fatigue failure mechanism in Ni‐based Superalloy

Abstract: The influence of residual compressive stress (RCS) depth and magnitude generated through surface treatments such as shot peening (SP), deep cold rolling (DCR), and vibro-peening (VP) on fatigue crack mechanisms of Ni-based superalloy is investigated. The fatigue performance with associated failure mechanisms is measured under strain-controlled fatigue testing upto 10 4 cycles with total strain in the range of 0.9%-1.4% at an R ratio of 0.1 and 400 C followed by load controlled fatigue until failure. In-depth u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…A potential solution lies in another surface enhancement technique known as deep cold rolling (DCR) which utilizes the pressure input from a hydrostatic bearing rather than a shot media. This effectively provides a smoother surface following treatment than shot peening while still imparting beneficial compressive residual stresses and surface hardening effects [2,[9][10][11]. Additionally, DCR is known to introduce less cold work than shot peening which enables higher stability of residual stresses under high temperature exposure [12,13].…”
Section: Surface Enhancement Techniquesmentioning
confidence: 99%
“…A potential solution lies in another surface enhancement technique known as deep cold rolling (DCR) which utilizes the pressure input from a hydrostatic bearing rather than a shot media. This effectively provides a smoother surface following treatment than shot peening while still imparting beneficial compressive residual stresses and surface hardening effects [2,[9][10][11]. Additionally, DCR is known to introduce less cold work than shot peening which enables higher stability of residual stresses under high temperature exposure [12,13].…”
Section: Surface Enhancement Techniquesmentioning
confidence: 99%
“…Moreover, the Kitagawa–Takahashi diagram of the laser‐peened specimens showed that the defect tolerance of the aluminum alloy was improved by such a treatment. Kumar et al 11 investigated the effect of residual compressive stress depth and magnitude produced by surface treatments such as SP, deep cold rolling (DCR), and vibro‐peening (VP) on fatigue crack mechanisms of a Ni‐based superalloy. Fatigue testing, performed at 400°C, was under strain‐controlled tension–tension loading mode, with a strain range between 0.9% and 1.4% and a loading ratio equal to 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the number of high cycle loads superimposed on the low cycle loads will lead to a significant decrease in the fatigue life under CCF loading. The LCF life, HCF life, and stress amplitude of high and low cycle loading have a relatively large influence on the fatigue life under CCF loading, and the influence is complex; therefore, the specific laws are not easy to obtain through experiments 26–36 …”
Section: Introductionmentioning
confidence: 99%
“…The LCF life, HCF life, and stress amplitude of high and low cycle loading have a relatively large influence on the fatigue life under CCF loading, and the influence is complex; therefore, the specific laws are not easy to obtain through experiments. [26][27][28][29][30][31][32][33][34][35][36] In practical engineering applications, since the calculation method of Miner's rule is simple, and the estimated fatigue life error can meet manufacturing demand, it is often used to predict fatigue life. [37][38][39][40][41] With the improvement of the reliability requirements of the mechanical structure, the life prediction error by the Miner's rule has attracted widespread attention.…”
Section: Introductionmentioning
confidence: 99%